Financial Literacy as a Determinant of Community Welfare: Empirical Evidence from a Rural Context - Ali, Fatria N.; Panigoro, Meyko; Koniyo, Rierind; Hasiru, Roy; Damiti, Fatmawaty (Journal of Economic Education and Entrepreneurship Studies, 2025)
The purpose of this study is to determine the effect of Financial Literacy on the Welfare of the Community in Titidu Village, Kwandang District, North Gorontalo Regency. This research uses a descriptive quantitative approach with a sample size of 44 people. The instrument used is a questionnaire or survey. The data analysis technique employed is simple linear regression analysis. Based on the results of the simple regression analysis, it can be seen that there is a positive and significant effect of financial literacy on the welfare of the community in Titidu Village, Kwandang District, North Gorontalo Regency. The regression analysis shows a coefficient of determination of 0.434, indicating that 43.4% of the variation in community welfare is influenced by financial literacy. This indicates a positive relationship between financial literacy and community welfare, where the better the financial literacy, the higher the community welfare. The remaining 56.6%, or the residual value, is influenced by other factors not examined in this study.